Building Resilience Among College Students: A Cross-Cultural Investigation on the Importance of Quality Crisis Communication and Social Support - Ndone, James (International Journal of Mass Communication, 2024)
Building on job demands-resources (JD-R model) and the social support theory, this study investigates how perceived quality of crisis communication and social support influence perceived uncertainties, emotional exhaustion, and resilience among college students in Kenya and the United States during the COVID-19 crisis. Data were collected using a survey (N= 394). The results indicate that higher perceived quality of crisis communication is associated with lower perceived uncertainties about the COVID-19 crisis. Both peer and advisor support are found to reduce students' perceived uncertainties. Notably, Kenyan students reported receiving more peer support compared to American students, while American students reported higher levels of advisor support. Additionally, perceived uncertainties mediated the relationship between advisor support and emotional exhaustion. Contrary to expectations, organizational intransigence did not moderate the relationship between social support and perceived uncertainties. Finally, a positive association was observed between perceived quality of crisis communication and resilience among students. These findings suggest the importance of effective crisis communication and social support in fostering resilience among students, with implications for both policy and practice across different cultural contexts.